Stiffness-matched biomaterial implants for cell delivery: clinical, intraoperative ultrasound elastography provides a 'target' stiffness for hydrogel synthesis in spinal cord injury. (July 2020) - Prager, Jon; Adams, Christopher F; Delaney, Alexander M; Chanoit, Guillaume; Tarlton, John F; Wong, Liang-Fong; Chari, Divya M; Granger, Nicolas
Safe hydrogel delivery requires stiffness-matching with host tissues to avoid iatrogenic damage and reduce inflammatory reactions. Hydrogel-encapsulated cell delivery is a promising combinatorial approach to spinal cord injury therapy, but a lack of in vivo clinical spinal cord injury stiffness measurements is a barrier to their use in clinics. We demonstrate that ultrasound elastography – a non-invasive, clinically established tool – can be used to measure spinal cord stiffness intraoperatively in canines with spontaneous spinal cord injury. In line with recent experimental reports, our data show that injured spinal cord has lower stiffness than uninjured cord. We show that the stiffness of hydrogels encapsulating a clinically relevant transplant population (olfactory ensheathing cells) can also be measured by ultrasound elastography, enabling synthesis of hydrogels with comparable stiffness to canine spinal cord injury. We therefore demonstrate proof-of-principle of a novel approach to stiffness-matching hydrogel-olfactory ensheathing cell implants to 'real-life' spinal cord injury values; an approach applicable to multiple biomaterial implants for regenerative therapies.